Pelvic inflammatory disease - Práxedes Rojas Quintana; Armando Bernia González; Santiago Bernia Sarría; Yunier Montalvo González; Teresa Oliva Rivero; Regla Fang Mederos (Medisur, 2007)
A bibliographical revision on the main topics referred to the acute pelvic inflammatory disease which includes definition, risk factors, diagnosis, and treatment with the objective to create a supporting educational aid to the teaching of students of 4th and 6th year of the medicine and nursing specialty in their rounds on the services of gynecology and obstetrics.